FACTORS INFLUENCING STUDENTS’ UNWILLINGNESS TO SPEAK IN EFL CLASSROOM - Marewangang, Resky Shafira; Asriati, Asriati; Sudding Sally, Fauzan Hari (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
The purposes of this research are to 1) find out the influencing factors of the students' unwillingness to speak in EFL classroom. and 2) find out how the factors influence students' unwillingness to speak in EFL classroom. A mixed-methods approach was used. The research subjects were 10th grade students majoring in Agribusiness Processing of Agricultural Products at SMK Negeri 4 Jeneponto. Participants were selected through a purposive sampling technique in determining the sample of this research, nine students were selected as participants, with three students categorized as having low score in English practice, three students categorized as having intermediate score in English practice, and three students categorized as having high score in English practice. The results of the research showed that psychological factor influencing students' unwillingness to speak in EFL classroom is lack of self-confidence. Meanwhile, linguistic factors included: (1) Lack of vocabulary (2) Lack of grammatical pattern knowledge and (3) Incorrect Pronunciation. A lack of confidence, frequently rooted in past negative experiences of language errors that have resulted in reluctance to speak in public, is a significant psychological barrier, discouraging students from participating. Linguistic challenges further exacerbate this issue; limited vocabulary and insufficient knowledge of grammatical patterns lead to hesitation and fragmented speech, as students struggle to articulate their thoughts clearly. Pronunciation errors also play a crucial role, as they can affect intelligibility and cause students to fear that their speech may not be understood, thus reinforcing their unwillingness to speak up in class.